Understanding the subcontractor’s submission to decennial liability in Algerian Law - Boulberdaa, Nehla (Journal of Human Sciences, 2020)
This paper seeks to address how the subcontractor becomes subjected to the decennial liability as it is a strict liability that makes the contractor and the architect responsible for the potential collapse of the building for a period of ten years.Afterward, the concept was expanded to include another actor, namely the subcontractor who was not concerned by this legislative before, because, firstly the subcontract makes the original contractor responsible for his work towards the employer and secondly due to the absence of the contractual relationship, in addition, the main objective is to protect the employer as he ignores the art of construction and manufacturing, also protecting the public interest.Indeed, this study aims to clarify the different measures took by the Algerian legislator after he has engaged the subcontractor in decennial liability regarding real estate development, for the purpose to protect the principal contractor and preserving the public interest.